Memahami Makna Simbol Dalam Proses Komunikasi - Abdul Rani Usman (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2024)
The communication process in everyday life cannot be separated from language and symbols. Symbols are seen as sensory expressions of transcendent reality in systems of logic and science. Symbols have meaning as abstract signs. A symbol is something that is considered by common agreement to be an image of reality and thought. This article examines the meaning of symbols in everyday communication processes. The results of this study are that symbols are a means of conveying aspirations for a group and/or symbols as well as references and patterns in acting and working for us on a daily basis. In this way, the symbol becomes important in life and life, besides that the symbol is of incomparable value, namely expressing messages for certain communicants.